The role played by perivascular cells in kidney interstitial injury - Rojas, Andres (Clin Nephrol, 2012)
Fibrosis of the kidney is a disease affecting millions worldwide and is a harbinger of progressive loss of organ function resulting in organ failure. Recent findings suggest that understanding mechanisms of development and progression of fibrosis will lead to new therapies urgently required to counteract loss of organ function. Recently, little-known cells that line the kidney microvasculature, known as pericytes, were identified as the precursor cells which become the scar-forming myofibroblasts. Kidney pericytes are extensively branched cells located in the wall of capillaries, embedded within the microvascular basement membrane, and incompletely envelope endothelial cells with which they establish focal contacts. In response to kidney injuries, pericytes detach from endothelial cells and migrate into the interstitial space where they undergo a transition into myofibroblasts. Detachment leads to fibrosis but also leaves an unstable endothelium, prone to rarefaction. Endothelial-pericyte crosstalk at the vascular endothelial growth factor receptors and platelet derived growth factor receptors in response to injury have been identified as major new targets for therapeutic intervention.